Rational Design of Pepsin for Enhanced Thermostability via Exploiting the Guide of Structural Weakness on Stability - Zhao, Yue; Miao, Yulu; Zhi, Fengdong; Pan, Yue; Zhang, Jianguo; Yang, Xuepeng; Zhang, John Z. H.; Zhang, Lujia (Frontiers in Physics, 2021)
Enzyme thermostability is an important parameter for estimating its industrial value. However, most naturally produced enzymes are incapable of meeting the industrial thermostability requirements. Software programs can be utilized to predict protein thermostability. Despite the fast-growing number of programs designed for this purpose; few provide reliable applicability because they do not account for thermodynamic weaknesses. Aspartic proteases are widely used in industrial processing; however, their thermostability is not able to meet the large-scale production requirements. In this study, through analyzing structural characteristics and modifying thermostability using prediction software programs, we improved the thermostability of pepsin, a representative aspartic protease. Based on the structural characteristics of pepsin and the experimental results of mutations predicted by several energy-based prediction software programs, it was found that the majority of pepsin’s thermodynamic weaknesses lie on its flexible regions on the surface. Using computational design, mutations were made based on the predicted sites of thermodynamic weakness. As a result, the half-lives of mutants D52N and S129A at 70°C were increased by 200.0 and 66.3%, respectively. Our work demonstrated that in the effort of improving protein thermostability, identification of structural weaknesses with the help of computational design, could efficiently improve the accuracy of protein rational design.